Effect of the Method of Processing and Preservation on Some Quality Parameters of Three Non-Conventional Leafy Vegetables - Aba Ejoh, Richard; Nkonga, Djuikwo Viviane; Inocent, Gouado; Moses, Mbofung Carl (Pakistan Journal of Nutrition, 2007)
In order to determine the best and cheapest method of processing that will minimize nutrient loss, and preserve the sensory characteristics, the effect of different processing and preservation methods on the mineral composition of and sensory properties of Vernonia amygdalina, V. colorata and V. calvoana var. non bitter were studied. These leafy vegetables were subjected to intense squeeze-washing and crushing, and boiling with different concentrations of Kanwa. Results show that these species are good sources of mineral and that V. colorata was richest in iron (15.22 mg DW/100g). All the other minerals had losses with a maximum of 56% recorded for calcium when V. amygdalina was boiled and squeeze-washed. Processing with natron resulted in smaller losses in minerals and in some cases slight increases (maximum of 9.5%) were observed for iron and phosphorus). Calcium, phosphorus and iron levels appeared to be dependent on the type of processing methods used and not the drying techniques or freezing time used in the process. The green colour and the texture of the samples boiled with kanwa are most preferred. Equally and better preferred are frozen vegetables as compared to the dried.